The effect of long-distance bicycling on ulnar and median nerves - An electrophysiologic evaluation of cyclist palsy - Akuthota, V.; Plastaras, C.; Lindberg, K.; Tobey, J.; Press, J.; Garvan, C. (The American Journal of Sports Medicine, 2005)
Background: Distal ulnar neuropathies have been identified in cyclists because of prolonged grip pressures on handlebars. The so-called cyclist palsy has been postulated to be an entrapment neuropathy of the ulnar nerve in the Guyon canal of the wrist. Previous studies utilizing nerve conduction studies have typically been either case reports or small case series.